A study in green hotels in the Klang area: the mediation effect of satisfaction between green marketing practices and hotel revisit intention / Shahir Fadzil, Rasidah Hamid and Hanafi Ong - Fadzil, Shahir; Hamid, Rasidah; Ong, Hanafi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
As sustainability gains prominence in the hospitality industry, the concept of green marketing has emerged as a strategic tool for hotels to differentiate themselves and attract environmentally conscious guests. Although in recent years, green practices have received considerable interest in the tourism industry, there is a lack of studies that explore satisfaction as a mediator in the Stimulus-Organism- Response (S-O-R) theory. The Klang area has won two international awards for its green initiatives. Hence, this conceptual paper explores the mediation effect of satisfaction between green marketing practices and hotel revisit intention in green hotels located in the Klang area. Drawing upon the S-O-R theory, this study aims to enhance our knowledge of how green marketing practices influence customer behavior, and ultimately their intention to revisit a sustainable hotel. By examining the mediating role of satisfaction, this paper contributes to the existing literature on green marketing and sustainable hospitality, providing practical insights for hotel managers and marketers seeking to enhance customer satisfaction and encourage hotel revisit intention.